Dynamics of Globalization’s Impact on Democratic Reality: A Study of ‎the Jordanian and Saudi Cases - khazali, mohammad Qasem (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to analyze the potential impact of globalization on democracy, highlighting how globalization can both promote and undermine democratic practices. It also sought to balance these contrasting effects to determine which trend more accurately reflects the general trajectory of the phenomenon. Methods: The study employed several methodologies to test its hypothesis, including statistical analysis to explore the relationship between globalization and democracy levels, trend analysis to track changes in democracy rates over time, and a comparative approach to assess the impact of globalization on democracy in Jordan and Saudi Arabia. Results: The findings indicate that globalization positively influences democracy at the global level. Specifically, the study showed that the impact of globalization on democracy rates in both Jordan and Saudi Arabia is positive. However, it found that the strength of this impact is statistically moderate in Jordan, while it is statistically weak in Saudi Arabia. Conclusion: The study concluded that the slow response of the political systems in Jordan and Saudi Arabia to the democratization pressures brought by globalization is one of the key factors explaining why globalization has not significantly impacted democracy rates in these two countries. It also warned that such delayed responses could negatively affect future political stability in both cases.